Business cycle accounting for the German fiscal stimulus program during the Great Recession - Daniel Fehrle; Johannes Huber (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
We take the neoclassical perspective and apply the business cycle accounting method as proposed by Chari, Kehoe, and McGrattan (2007, Econometrica) for the Great Recession and the associated stimulus program in Germany 2008-2009. We include wedges to the variables government consumption, durables, investment, labor, net exports, and efficiency. The results suggest: The crisis was mainly driven by the efficiency wedge, followed by the net exports and the investment wedge. The government consumption wedge and in particular the durables wedge acted counter-cyclical. We attribute the latter to an internationally incomparably large cash for clunkers program and conclude that this subsidy on durable goods was more effective than pure government consumption. We introduce a strategy for likelihood maximization, which reliably and quickly locates the maximum; enables a detailed evaluation of the likelihood function and allows large robustness checks.
Keywords: C32; E20; E32; H12; H31; 330; Fiscal stimulus; Great Recession; Business cycle accounting; Maximum-Likelihood